Performativity of JaF art agency on the land, city, and its surroundings - Sudarmanto, Joni Agung (Fakultas Sastra Universitas Negeri Malang, 2024)
This study aims to see the performativity of terracotta through the process and the culture of the roof tile production industry in Jatiwangi District, Majalengka Regency, West Java. This research used qualitative methods, and collecting data used a combination of three methods: literature study, participatory observation, and semi-structured interviews. After the data is collected, the next step is data analysis using the concept of performativity and art agency. JaF emerged by taking on the role of a change agent, inviting Jatiwangi residents, especially roof tile industry players, to survive together and stay true to their native culture using participatory arts engagement. Perform various artistic activities with Jatiwangi residents to declare that they exist. They are using artistic approaches to narrate defensive actions, holding various forms of art festivals to show their progress in Jatiwangi. This is due to the performativity of roof tiles as the initial trigger, the community, and the development of Jatiwangi as an